Prevalence, knowledge, attitudes, and practices concerning self-medication with over-the-counter drugs among university students in Jordan: A cross-sectional study - Abdallah Y. Naser (PLoS ONE, 2026)
Background The World Health Organization considers self-medication (SM) a critical global concern. SM has significant risks, including incorrect drug use, adverse reactions, misdiagnosis, and increased antibiotic resistance. The prevalence of SM is particularly high in developing countries, where students can purchase medications without medical supervision. This study investigates the prevalence of SM practices using over-the-counter (OTC) drugs and their associated predictors. Additionally, this study explores the knowledge, attitudes, and practices of university students in Jordan regarding SM. Method A cross-sectional online survey study was conducted among university students in Jordan from March to September 2024. The questionnaire was distributed among university students through online social media platforms (Facebook, WhatsApp, and Instagram). To identify predictors of SM practice among university students, binary and multiple logistic regression analyses were implemented. A Chi-squared test was used to estimate the risk of SM among students. Results Of 1,269 university students participating, 45.3% reported practicing SM. Knowledge about OTC drug safety was generally high, as most students identified the risks of combining OTC and prescription medications (83.5%) and the importance of avoiding expired drugs (95.5%). Medical students demonstrated significantly better knowledge of diseases manageable by OTC drugs and the likelihood of side effects (p < 0.001). Attitudes varied; the majority of students (71%) agreed that a doctor should be consulted before using OTC medications, pharmacists were the primary source of advice (51.2%), and antipyretics were the most commonly used medications (46.9%). Multiple logistic regression provided evidence that fifth-year students were significantly more likely to practice SM (adjusted odds ratio (aOR) = 2.38, p = 0.021). No other demographic variable was statistically associated with this practice. Conclusion Fifth-year students exhibited a significantly higher estimated risk of practicing SM compared to their peers in other academic years. This highlights the need for targeted educational interventions to promote safe SM practices. These findings highlight the need for targeted educational interventions. However, the use of self-reported data is a limitation that may introduce recall or reporting bias.